Effect of CeO2 for a high-efficiency CeO2/WO3–TiO2 catalyst on N2O formation in NH3-SCR: a kinetic study. Issue 9 (15th December 2015) - Geng, Yang; Shan, Wenpo; Xiong, Shangchao; Liao, Yong; Yang, Shijian; Liu, Fudong
Abstract : The effect of CeO2 for a high-efficiency CeO2 /WO3 –TiO2 catalyst on N2 O formation in NH3 -SCR reaction was investigated using a kinetic method. Abstract : In this study, we investigated the effects of CeO2 for a high-efficiency CeO2 /WO3 –TiO2 catalyst on N2 O formation in NH3 -SCR reaction using a kinetic method. The results demonstrated that CeO2 is very effective for enhancing the SCR (4NH3 + 4NO + O2 → 4N2 + 6H2 O) reaction rate and thus suppressing the NSCR reaction (4NH3 + 4NO + 3O2 → 4N2 O + 6H2 O) due to the competition between these two reactions. Therefore, N2 O formation under SCR reaction conditions could be remarkably inhibited with the addition of CeO2 to the catalyst. On the other hand, CeO2 can also enhance the C–O reaction (4NH3 + 5O2 → 4NO + 6H2 O) over the catalyst, so N2 O formation under NH3 oxidation conditions was promoted due to the lack of SCR reaction. In addition, we also found another interesting phenomenon wherein N2 O formation over WO3 –TiO2 (without CeO2 ) decreased gradually at high temperature from 350 to 450 °C, while N2 O formation over CeO2 /WO3 –TiO2 kept increasing with the reaction temperature, which was also associated with the promotional effect of CeO2 on SCR reaction and the competition between SCR and NSCR reactions.